2022
DOI: 10.3389/fendo.2022.1029041
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the “3 Ps”: A critical appraisal of the non-endocrine manifestations of multiple endocrine neoplasia type 1

Abstract: Multiple endocrine neoplasia type 1 (MEN1), an autosomal-dominantly inherited tumor syndrome, is classically defined by tumors arising from the “3 Ps”: Parathyroids, Pituitary, and the endocrine Pancreas. From its earliest descriptions, MEN1 has been associated with other endocrine and non-endocrine neoplastic manifestations. High quality evidence supports a direct association between pathogenic MEN1 variants and neoplasms of the skin (angiofibromas and collagenomas), adipose tissue (lipomas and hibernomas), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 171 publications
0
8
0
Order By: Relevance
“…The association between a variety of cutaneous lesions (i.e., angiofibromas, collagenomas, and lipomas) and MEN1 syndrome was first reported in 1997 by Darling et al (20) and has been confirmed in subsequent studies (39,40). Biopsies of facial angiofibromas, lipomas, and collagenomas from patients harboring germline MEN1 variants exhibited an allelic deletion of chromosome 11 including the MEN1 locus (24).…”
Section: Discussionmentioning
confidence: 89%
“…The association between a variety of cutaneous lesions (i.e., angiofibromas, collagenomas, and lipomas) and MEN1 syndrome was first reported in 1997 by Darling et al (20) and has been confirmed in subsequent studies (39,40). Biopsies of facial angiofibromas, lipomas, and collagenomas from patients harboring germline MEN1 variants exhibited an allelic deletion of chromosome 11 including the MEN1 locus (24).…”
Section: Discussionmentioning
confidence: 89%
“…It is generally known that anterior mediastinal lesions in MEN1 male patients should be considered thymic carcinoids until proven otherwise because carcinoid tumors have a relatively poor prognosis. Nevertheless, patients affected by MEN1 should be aware of these nonendocrine manifestations, and providers should always be encouraged to think beyond the "3Ps" when treating a MEN1 patient [3]. Thymoma is supposed to be noticed in MEN1, and the diagnosis of a thymoma should prompt further evaluation of a possible underlying MEN1 syndrome, especially for a thoracic surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The three main manifestations of MEN1 (known as 3Ps) are primary hyperparathyroidism (PHPT), gastroenteropancreatic neuroendocrine tumors (NETs), and anterior pituitary adenomas (PAs), which have a lifetime prevalence of 95%, 80%, and 50%, respectively. An increasing number of atypical MEN1 tumors have been found over the years, including but not limited to thymic and bronchial carcinoid tumors, breast tumors, and uterine tumors [3]. Among these tumors, most thymic epithelial tumors in MEN1 are thymic carcinoids.…”
Section: Introductionmentioning
confidence: 99%
“…MEN1 pathogenic variants in exon 2, 9, and 10 are prone to a more aggressive pancreatic NET behavior [ 72 ]. Other nonendocrine components have been placed in relationship with MEN1 like breast cancer or melanoma, but currently, there is insufficient statistical evidence to directly connect them with the MEN1-associated picture [ 89 , 90 ].…”
Section: Introductionmentioning
confidence: 99%